The THE INFLUENCE OF BRAND IMAGE AND PRODUCT INNOVATION ON STARBUCKS COFFEE PURCHASE DECISIONS IN SURABAYA CITY - Agus - Baktiono (IJEBD (International Journal of Entrepreneurship and Business Development))
Along with the urban lifestyle, the development and growth of culinary businesses are currently increasing in Indonesia, especially in the city of Surabaya, this is marked by the rise of restaurants, cafes and coffee shops. Starbucks Coffee Indonesia now has 22 coffee outlets in the city of Surabaya. Starbucks strives to present an extraordinary legacy and experience in every cup.